Salt-tolerant alternative crops as sources of quality food to mitigate the negative impact of salinity on agricultural production - Egea, Isabel; Estrada, Yanira; Faura, Celia; Egea-Fernández, José M.; Bolarin, Maria C.; Flores, Francisco B. (Frontiers in Plant Science, 2023)
Generation of crops with enhanced abiotic stress tolerance and high nutritive value is a priority in present-day agriculture because of climate change and rising world population. Among abiotic stresses, yield losses due to cultivation in saline soils is an ever-increasing pressing problem in agriculture. Mounting urbanisation and industrialization, and increasing global food demand, is pressing farmers to make use of marginal lands affected by salinity and low-quality saline water. A better understanding of the effects of salinity on crop production and quality is crucial, in particular the challenges that plants have to overcome when growing under salt stress. To overcome these challenges, one of the most promising approaches is searching for new sources of genetic variation like underexploited crops, which are locally important crops grown in restricted regions of the world. They are generally less efficient than cultivated crops in optimal conditions due to lower yield but represent an alternative in stressful growth conditions and constitute a broad gene pool for crop breeding, having a remarkably potential to contribute to food security. In this review we summarize what is known and what advances should be achieved in order to revalorize underexploited species differing in their genetic nature. First, we highlight advances in research on salt tolerance of traditional varieties of tomato or landraces; varieties selected and developed by smallholder farmers for adaptation to their local environments showing specific attractive fruit quality traits. We remark advances attained in screening a collection of tomato traditional varieties gathered in Spanish Southeast, one of the most productive regions which environment is extremely stressing. Second, we explore the opportunities of exploiting the natural variation of halophytes, in particular the Amaranthaceae, which comprises by far the highest proportion of salt-tolerant halophytic crop species, where quinoa and amaranth stand out. The adaptation of both species in stressful growth conditions is becoming an increasingly important issue, especially for their cultivation in arid and semiarid areas prone to be affected by salinity. Here we present a project developed in Spanish Southeast, where quinoa and amaranth varieties are being adapted for their culture under abiotic stress targeting high quality grain.